Revalidation of preservice physical education teacher’s teacher identity scale in Chinese physical education student teachers - Yang, Anlu; Wang, Yongshun; Yao, Lei; Hamilton, Xiaofen D. (Frontiers in Psychology, 2023)
Teacher identity (TI) is a crucial aspect to pre-service physical education teachers (PPETs) to becoming high quality teachers and plays an important role their career choice. Thus, a deep understanding of their TI may help improve the quality of future PE teachers. This study aimed to provide further evidence of reliability and validity for Preservice Physical Education Teacher’s Teacher Identity Scale. After having re-examined the content validity, the domain of affects was deleted. The modified scale then consisted of the three domains (i.e., value and expectation, perceived confidence of teaching PE, and professional growth). A total of 944 physical education student teachers in China participated in the study. Confirmatory factor analysis (CFA) was employed to investigate the construct validity, the results suggested the data did not fit the original model. After the unfitted item was excluded. All CFA fit indices were within the acceptable range. Reliability of the scale was then examined by calculating G-C alphas. The alpha values were within the acceptable range. The modified model was reliable and valid. The revalidation of the scale provided more us with a scale that could produce reliable and valid score measuring PPETs’ TI.